Preparation and inter-Band Transition of Zno Thin Films by an Evaporation Method (مجلة ديالى للبحوث الانسانية, 2022)
Transparent zinc oxide (ZnO) thin films have been prepared on a glass substrate at 450 OC by thermal evaporation.Structural and optical properties were studied. X-ray diffraction studies showed the polycrystalline nature of the films with preferred (002) orientation perpendicular to substrate surface and grain size estimated to be 40 nm. The optical absorption coefficient, Urbach energy, energy gap were determined from transmittance spectrum in the wavelength range (300 - 900) nm.